Effectiveness of the muscle energy technique on respiratory muscle strength and endurance in patients with fibromyalgia - Uysal, Stimeyye Cildan; Tuzun, Emine Handan; Eker, Levent; Angin, Ender (Ios Press, 2019)
BACKGROUND: Fibromyalgia is characterized by a chronic and common musculoskeletal system pain that affects cervical mobility and inspiration. This may cause changes in thoracic mechanics. OBJECTIVE: To investigate the effectiveness of the muscle energy technique applied to cervical accessory respiratory muscles on respiratory muscle strength and endurance in patients with fibromyalgia. METHODS: The participants were 37 women diagnosed with fibromyalgia. They were assessed for their respiratory muscle strength, respiratory muscle endurance, pain and fatigue severity, flexibility and disability. The muscle energy technique was applied to the scalene, upper trapezius, and sternocleidomastoid muscles after a superficial heat application. The treatment was continued for 3 weeks with 3 sessions per week. RESULTS: After the treatment, expiratory muscle strength and respiratory muscle endurance increased significantly. Severity of pain and fatigue and disability were reduced, cervical flexibility increased significantly (p < 0.05). The effect size was r >= 0.4 for all the variables. CONCLUSION: The muscle energy technique applied to cervical accessory respiratory muscles in patients with fibromyalgia who had complaints in the neck and back region positively increased respiratory muscle strength and endurance, cervical flexibility, and decrease pain intensity, fatigue and disability. It is recommended that subsequent randomized studies are carried out with a placebo control group.
Keywords: Respiratory muscle strength; respiratory muscle endurance; pain intensity; cervical flexibility; fatigue; disability